Managing ensemble scale heritage conservation in the Shandon Architectural Conservation Area in Cork, Ireland. (February 2017) - Matthews, Tony; Grant-Smith, Deanna
Highlights: Paper explores use of planning frameworks in ensemble scale urban conservation. Ensemble scale conservation focuses on urban character beyond individual buildings. Interrelated physical, spatial, social dimensions require sensitive management. Planning-led conservation efforts targeting ensembles are inherently political.